The suicidal patient clinical and legal standards of care - Bongar, Bruce Michael (American Psychological Association, 2013)
Suicide is uncomfortable to talk about, and many prefer to sweep the topic under the rug; but suicide remains a serious public health problem. This third edition of The Suicidal Patient by Bruce Bongar and Glenn Sullivan will prove to be an essential and vital resource for clinicians, supervisors, attorney, and clinicians in training"--Foreword. (PsycINFO Database Record (c) 2014 APA, all rights reserved)